PELATIHAN ECOPRINT TEKNIK POUNDING UNTUK SISWA SEKOLAH DASAR - Widiastuti, Theresia; Sulistyati, Apika Nurani; Setyawan, Setyawan; Darwoto, Darwoto; Dartono, Felix Ari (Adi Widya : Jurnal Pengabdian Masyarakat, 2023)
Ecoprint is a technique of giving patterns on fabrics made from natural materials which aims to reduce the negative impact on the environment. The activity of making environmentally friendly ecoprint crafts on drawstring bags using the pounding technique was carried out with fifth grade students of SDN Cemara Dua Surakarta. Extra-curricular activities are routinely carried out by schools, one of which aims to maintain environmental preservation and prevent damage to the environment and pollution of the school. Through this activity it is hoped that students will acquire a simple provision of knowledge about nature, especially plants. The pounding process that was trained on them used kenikir leaves which have a variety of nutritional content and are beneficial for health, besides having a unique color when tapped on the cloth. New things that can be valuable input for elementary school students besides gaining skills to make crafts that can be used alone. The method used in this service activity is in the form of training. Students are provided with very basic simple knowledge about plants, understand the process of making works using the pounding technique, learn to make beautiful patterns by arranging kenikir leaves on the surface of drawstring bags, and produce eco-friendly crafts. In this activity the service team accompanies each student to work while playing in the hope of awakening their creativity.